Enderleinellus kumadai Kaneko 1954 (ANOPLURA: ENDERLEINELLIDAE) PADA BAJING, Callosdurus notatus (RODENTIA: SCIURTOAE) - Hartini, Sri (Research Center for Biology-Indonesian Institute of Sciences, 2000)
-